2017
DOI: 10.1161/circinterventions.116.004762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Thrombogenicity for Metallic and Polymeric Bioabsorbable Scaffolds

Abstract: Despite a similar scaffold strut thickness, the Magmaris sirolimus-eluting bioabsorbable magnesium scaffold was significantly less thrombogenic compared with the Absorb bioresorbable vascular scaffold in an ex vivo porcine arteriovenous shunt model. Further studies are needed to determine whether the reduced thrombogenicity of Magmaris will result in reductions in major cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 25 publications
5
52
0
Order By: Relevance
“…Although angiographic and clinical outcomes were favorable in the BIOSOLVE‐II trial at 24‐months with no evidence of scaffold thrombosis , this real world case raises concern over potential early scaffold collapse due to insufficient radial strength. Despite the scaffold collapse leading to re‐stenosis and recurrent angina, the absence of thrombus formation is an important observation supporting low thrombogenicity of the magnesium scaffold as has been suggested by recent pre‐clinical studies .…”
Section: Discussionsupporting
confidence: 58%
“…Although angiographic and clinical outcomes were favorable in the BIOSOLVE‐II trial at 24‐months with no evidence of scaffold thrombosis , this real world case raises concern over potential early scaffold collapse due to insufficient radial strength. Despite the scaffold collapse leading to re‐stenosis and recurrent angina, the absence of thrombus formation is an important observation supporting low thrombogenicity of the magnesium scaffold as has been suggested by recent pre‐clinical studies .…”
Section: Discussionsupporting
confidence: 58%
“…Preclinical studies demonstrated that a sirolimus-eluting bioresorbable magnesium scaffold (Mg-BRS; MagMaris, Biotronik AG, Bülach, Switzerland) is associated with lower thrombogenicity and lower deposition of inflammatory cells compared to the polymeric Absorb BRS and to an equivalent (in geometry and design) 316-L stainless steel, thinner struts (60–80 μm), sirolimus-eluting (poly-L-lactic acid [PLLA] coating) stent (Orsiro, Biotronik AG) [1, 2]. Furthermore, encouraging clinical outcomes were reported within 24 months after MagMaris implantation in selected patients with stable or unstable angina [3].…”
mentioning
confidence: 99%
“…In particular, the PLLA-coated Mg-BRS has been shown to have superior endothelialization and decreased thrombus formation compared to both the Absorb BRS and the Orsiro DES in animal models [1, 2]. This may have occurred because the magnesium alloy composing the BRS struts is negatively charged, helping to repel negatively charged platelets and minimizing thrombogenicity [2].…”
mentioning
confidence: 99%
“…Compared to Absorb, Magmaris showed improved deliverability and thanks to the peculiar magnesium properties, a shorter reabsorption process . Furthermore, despite a similar scaffold strut thickness, Magmaris was significantly less thrombogenic compared with Absorb bioresorbable vascular scaffold in an ex vivo porcine arteriovenous shunt model . Encouraging results were published by Haude et al who reported no scaffold thrombosis at 24 months of follow‐up in 193 patients with stable and unstable angina included in the BIOSOLVE II study .…”
Section: Discussionmentioning
confidence: 95%